Detection of DNA Gyrase Mutation and Multidrug Efflux Pumps Hyperactivity in Ciprofloxacin Resistant Clinical Isolates of Pseudomonas aeruginosa - Abolghasem Tohidpour; Shahin Najar Peerayeh; Sarah Najafi (Pasteur Institute of Iran, 2013)
Target modification and reduced drug accumulation are the main resistance mechanisms against fluoroquinolone antibiotics in Pseudomonas aeruginosa. We performed a genotypic characterization of three major Mex multidrug efflux pumps (MexAB-OprM, MexXY-OprM and MexCD-OprJ) in ciprofloxacin resistant clinical isolates of P. aeruginosa, collected from Tehran, Iran this was followed by sequencing and analyzing the type II topoisomerases encoding gyrA, gyrB, parC , and parE genes. Reverse transcription PCR (RT-PCR) and semi-quantitative RT-PCR methods were used to analyse the transcription of efflux pumps. Topoisomerase mutation analysis was carried out through PCR amplification and sequencing of the quinolone resistance determining region (QRDR) of the topoisomerases encoding genes. Some 11.1% of the strains actively expressed MexCD-OprJ and 15.5% hyperexpressed MexXY-OprM efflux pumps. No overexpression was detected for MexAB-OprM, whereas 4.4% of strains showed simultaneous expression of MexCD-OprJ and MexXY-OprM. In the sequencing results, a single point mutation in the QRDR of gyrA was detected in all tested strains, where Isoleucine was substituted by Threonine at position 83. No mutations were detected in QRDR of gyrB, parC and parE genes. We are the first to report the genotypic analysis of ciprofloxacin mediated efflux pump resistance from Iran. These findings emphasize the clinical significance of multidrug efflux pumps and topoisomerases mutations activity in conferring resistance to fluoroquinolone antibiotics, and support the use of genotypic methods for analysis of resistance elements in P. aeruginosa in developing countries such as Iran.